Principles of the Qur’anic and Political Ideology of Imam Khomeini - Arash Daneshmehr; Reza Ramezani (سپهر سیاست, 2020)
The purpose of the present article is to research about the principles of Imam Khomeini’s political ideology. The method of study is descriptive analysis and the results showed that in his doctrine, every political attempt is divided into Godly and non-Godly. He holds that if the attempts of administrators, leaders, social planners and reformers target people’s prudence, spirituality, and convenience, their politics would be recognized as Godly. Therefore, if the leaders adhere to the political traditions of Ahl al-Bayt, their decisions would be for God; otherwise, it would be for evil. Imam Khomeini in some of his speech emphasizes that the main mission of the holy prophets and saints has not been the establishment of a government because they have verily come for the ethical and spiritual treatment and purification of human being. Yet, he acknowledges social administration and political order in human society as a serious and inevitable issue such that he recognizes the Qur’an as a combination of spiritual gnosis and plans for human being as well as a comprehensive book for the governments. He holds that the relation between social verses compared to religious verses in the Qur’an is even more than 10 to 1. Imam Khomeini who considers the Qur’an as the book of law, asserts that the nature of Qur’anic instructions implicitly emphasize the need to government and hence he believes in the necessity of political system and social order for the gnosis growth and spiritual progress of humans.